Measures of Positive Psychology Development and Validation - Singh, Kamlesh; Junnarkar, Mohita; Kaur, Jasleen; SpringerLink (Online service) (New Delhi : Springer India (Imprint), 2016)
The book contributes to the vast field of research in psychometrics as well as to the growing field of positive psychology. It analyses the development and validation of several constructs of positive psychology like resilience, flow, mindfulness, spirituality, and intrapersonal and interpersonal strengths. The chapters discuss the test construction process and develop scales for constructs that are validated on the Indian population. In most Indian behavioral research, psychological tests from the West are employed without assessing psychometric properties in India. However, establishing validation of psychological tests in a new culture is necessary in order to claim results based on these tests. Hence, this book bridges this gap in positive psychology and its allied fields and develops and standardizes these scales for the Indian population. The new constructed and validated scales have undergone rigorous statistical screening. Psychologists, psychiatrists, and social workers interested in studying well-being in India and in understanding how to create psychometric scales for non-Western populations will find the book useful for their research.
Chapter 1. Positive Psychology in India: A review -- Chapter 2. Norms in Test Construction -- Chapter 3. The Assessment of Resilience -- Chapter 4. Flow-Scale Construction & Validation -- Chapter 5. Mindfulness and its Assessment -- Chapter 6. Spirituality and its Assessment -- Chapter 7. Well-being and its Assessment -- Chapter 8. Development and Validation of new Interpersonal and Intrapersonal Strengths Measures.
Keywords: Quality of life -- Research; Psychiatry; Positive Psychology